Students’ View on English Assessment in Indonesia’s Merdeka Curriculum: A Kirkpatrick Evaluation Model - Khoiriyah, Nisa; Tarihoran, Naf’an; Fitriani, Dini (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Using Kirkpatrick's Four-Level Evaluation Model of reaction, learning, behavior, and results, this study investigates how students view English assessment in the Indonesian Merdeka Curriculum. This study involved 41 high school students who answered a valid and reliable Likert scale questionnaire, using a quantitative descriptive design. Students' perceptions were generally positive, according to descriptive statistical analysis conducted using SPSS 26. Most students acknowledged that the assessment was fair, relevant to classroom learning, and motivating. In addition, students reported behavioral changes such as increased classroom participation, but they experienced improvements in learning, especially in vocabulary and confidence. Although some students remained neutral, students said that the assessment helped their overall language development. The clarity of instructions, adequacy of time, and comfort during the assessment were also issues. These results indicate that, although the Merdeka Curriculum assessment method is in line with basic principles, some elements of practice need to be improved in order to optimize students' learning experiences and learning outcomes.